A simple method of recovery of mineral oil from waste cutting oil emulsions - Chakravarty, N. K.; Bhattacharya, D. C.; Banerjee, B. T. (Defence Science Journal, 2014)
A simple chemical method for recovery of mineral oil from waste cutting oil emulsions using a chemical which is wholly indigenous has been standardized. It has been established that requisite volume of 15% alum solution at 50/Degree/C results in complete oil separation irrespective of the nature of oil originally used for making the emulsions and the resulting emulsion composition. It has been found that the separated mineral oil is suitable for use as furnace fuel oil. A lay out of the plant required has been suggested and a construction cost estimate has been presented.